2021
DOI: 10.3389/fneur.2021.699844
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy Outcomes of Natalizumab vs. Fingolimod in Patients With Highly Active Relapsing-Remitting Multiple Sclerosis: Real-World Data From a Multiple Sclerosis Reference Center

Abstract: Background: Natalizumab (NTZ) and fingolimod (FTY) are second-line disease modifying treatments (DMTs) approved for Relapsing – Remitting Multiple Sclerosis (RRMS). Few studies are available on a direct comparison between NTZ and FTY, based on post-marketing experience, with conflicting results and reporting relatively short follow-up period.Aim: We hereby report real-world experience of a MS Center with respect to NTZ vs. FTY comparison in terms of efficacy and safety, referencing long-term follow-up.Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…When initiated early in the disease course, natalizumab was associated with fewer relapses and reduced disability worsening (Butzkueven et al, 2020a;Wiendl et al, 2021). The long-term effectiveness of natalizumab was also described in other real-world studies (Boziki et al, 2021;Davidescu et al, 2021;Efthimios et al, 2021;Guger et al, 2021;Horakova et al, 2020;Prosperini et al, 2017). Results from these studies indicate that, when administered long-term, natalizumab is effective and has an adequate safety profile, provided subjects are closely monitored.…”
Section: Long-term Efficacy and Safety Of Natalizumabmentioning
confidence: 83%
See 3 more Smart Citations
“…When initiated early in the disease course, natalizumab was associated with fewer relapses and reduced disability worsening (Butzkueven et al, 2020a;Wiendl et al, 2021). The long-term effectiveness of natalizumab was also described in other real-world studies (Boziki et al, 2021;Davidescu et al, 2021;Efthimios et al, 2021;Guger et al, 2021;Horakova et al, 2020;Prosperini et al, 2017). Results from these studies indicate that, when administered long-term, natalizumab is effective and has an adequate safety profile, provided subjects are closely monitored.…”
Section: Long-term Efficacy and Safety Of Natalizumabmentioning
confidence: 83%
“…Real-world cohorts of persons with RRMS from single centers, multicenters, and national and international registries have been well utilized to explore the comparative effectiveness of natalizumab with another highly effective DMT, fingolimod, across clinical, radiological, disability, and disease activity outcomes (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Braune et al, 2013;Curti et al, 2019;Guerra et al, 2021;Kalincik et al, 2015;Koch-Henriksen et al, 2017;Prosperini et al, 2017). The majority of these studies have shown natalizumab to be superior to fingolimod with regard to ARR, proportion of PwMS relapsing at 1 and 2 years and over longer time periods, short-term disability improvement, and proportions of PwMS with gadolinium (Gd)-enhancing lesions or new T2 lesions at 1 and 2 years (Barbin et al, 2016;Baroncini et al, 2016;Boziki et al, 2021;Kalincik et al, 2015).…”
Section: Comparative Effectiveness Of Natalizumab Versus Other Dmtsmentioning
confidence: 99%
See 2 more Smart Citations
“…Learned from the developmental history, not all, but many of the αv-inhibitors have an inherent nonspecific property with regard to binding of inhibitors to the target and engagement of the target integrin to ligands. In contrast, the integrin inhibitors already in the clinic, such as abciximab (targeting αIIbβ3 on platelets) [ 96 ], natalizumab (α4β1 on T-cells) [ 97 , 98 ], vedolizumab (α4β7 on T-cells) [ 99 ], and lifitegrast (αLβ2 on T-cells) [ 100 ] commonly bind specifically to their targets. Three of the inhibitors are target specific mAbs, and the other inhibitor, liftegrast, is localized in the site of pathology (dry eye) due to the nature of the ophthalmic solution.…”
Section: Future Directions For Anti-fibrotic Integrin Inhibitor Drugsmentioning
confidence: 99%